Cultural Tourist Attraction Potential Development guideline for province - Boonsot, Natthayot; Phaengsoi , Kosit (Community and Social Development Journal, 2021)
Objectives of study are 1) to study the development of cultural tourist attraction in Surin province. 2) to study the problem of Surin’s cultural tourist attraction. 3) to purpose the guideline to develop tourist attraction potential in Surin. The methods used in this research are discovering, observation, interviewing, group chat, and academic meetings. There are 93 samples from four cultural tourist attraction ; which are Ban Ta Klang, Ban Phumpone, Wat Khaosala and swamp eel, jasmine rice and red cross festival by using purposive sampling method. The results of the study were 1) In the development of cultural tourist attraction in Surin, the government sectors had supported the training for community. They created tourist management committee members in the community. People who are in the community can be in tourist management along with their lifestyle. And the community’s management can truly respond to community’s needs. 2) There were few problems in the cultural tourist attraction in Surin; Homestay hosts have problem with communicating foreigners with international language. They do not have enough translator and effective management in homestay. 3) The way of developing potential cultural tourist attraction can be divided into three aspects; development guideline general way of development, way of development from tourists’ needs and way of potential development in cultural tourist attraction. Lastly, the solutions are divided into three ways; tourist’s perception (attracting tourist), tourist carrying capacity and management.